Marker-Trait Association for Biomass Yield of Potential Bio-fuel Feedstock Miscanthus sinensis from Southwest China - Nie, Gang; Huang, Linkai; Zhang, Xinquan; Taylor, Megan; Jiang, Yiwei; Yu, Xiaoqing; Liu, Xinchun; Wang, Xinyu; Zhang, Yajie (Frontiers in Plant Science, 2016)
As a great potential bio-fuel feedstock, the genus Miscanthus has been widely studied around the world, especially Miscanthus × giganteus owing to its high biomass yield in Europe and North America. However, the narrow genetic basis and sterile characteristics of M. × giganteus have become a limitation for utilization and adaptation to extreme climate conditions. In this study, we focused on one of the progenitors of M. × giganteus, Miscanthus sinensis, which was originally distributed in East Asia with abundant genetic resources and comparable biomass yield potential to M. × giganteus in some areas. A collection of 138 individuals was selected for conducting a 3-year trial of biomass production and analyzed by using 104 pairs of SRAP, ISAP, and SSR primers for genetic diversity as well as marker-trait association. Significant differences in biomass yield and related traits were observed among individuals. Tiller number, fresh biomass yield per plant and dry biomass yield per plant had a high level of phenotypic variation among individuals and the coefficient of variation were all above 40% in 2011, 2012, and 2013. The majority of the traits had a significant correlation with the biomass yield except for the length and width of flag leaves. Plant height was a highly stable trait correlated with biomass yield. A total of 1059 discernible loci were detected by markers across individuals. The population structure (Q) and cluster analyses identified three subpopulations in the collection and family relative kinship (K) represented high gene flow among M. sinensis populations from Southwest China. Model testing identified that Q+K was the best model for describing the associations between the markers and traits, compared to the simple linear, Q or K model. Using the Q+K model, 12 significant associations (P < 0.001) were identified including four markers with plant height and one with biomass yield. Such associations would serve an efficient tool for an early selection of M. sinensis and facilitate a genetic improvement of biomass yield for this species.